Beyond Financial Metrics: A Systematic Review of Maqasid Based Performance Measurement in Islamic Banking - Mahfuz; Moh Asmawi; Nanda Khairiyah (Yayasan Darussalam Bengkulu, 2026)
Background: This study examines the development of maqasid al-shariah-based performance measurement in Islamic banking and addresses the limitations of existing approaches. Despite the rapid growth of Islamic banking, performance evaluation remains largely dominated by conventional financial indicators, which fail to capture the broader ethical and socio-economic objectives embedded in maqasid al-shariah. In response, various studies have proposed maqasid-based models; however, these approaches often reduce maqasid into static and fragmented indicators, limiting their conceptual and practical relevance. Method: This study employs a systematic literature review (SLR) approach, guided by the PRISMA framework, to analyze 15 selected studies published between 2015 and 2025. Results: The findings reveal that the existing literature is characterized by three major issues: the dominance of indicator-based measurement, the lack of interconnectedness among maqasid dimensions, and the absence of process-oriented evaluation. Additionally, the literature remains fragmented across multiple domains, including banking performance, socio-economic development, governance, and financial innovation. To address these limitations, this study proposes a reconstruction of maqasid-based performance measurement using a systems approach inspired by Jasser Auda. This approach conceptualizes maqasid as a dynamic and interconnected framework, emphasizing the relationships between inputs, processes, outputs, and outcomes. Conclusion: The study contributes to bridging the gap between normative maqasid theory and empirical application, offering a more holistic and integrative framework for evaluating Islamic banking performance. The findings also provide practical implications for regulators and practitioners in developing performance measurement systems that align with the ethical and socio-economic objectives of Islamic finance.